Cardiac fatigue following prolonged endurance exercise of differing distances - Whyte, G. P.; George, K.; Sharma, S.; Lumley, S.; Gates, P.; Prasad, K.; McKenna, W. J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Recent echocardiographic studies have reported cardiac dysfunction following ultra-endurance exercise in trained individuals. The duration of exercise required to elicit cardiac dysfunction and the mechanisms underlying this phenomenon have not been fully elucidated. The aim of the present study was to examine the presence of cardiac dysfunction following a half-Ironman and Ironman triathlon in trained individuals. Methods: 14 male triathletes (age: 32 ± 5 yr; height: 180 ± 8 cm; body mass: 75 ± 9 kg) completed a half-Ironman triathlon. Following a 4-wk period, 10 of the original 14 triathletes completed an Ironman triathlon. All triathletes were assessed using ECG, echocardiography, and blood analysis pre-, immediately post-, and 48 h postrace for both distances. Results: Echocardiographic results indicated diastolic and systolic left ventricular dysfunction, for both race distances, which were associated with altered relaxation characteristics and a reduced inotropic contractility, respectively. Following 48-h recovery, all echocardiographic measures were similar to resting values. Creatine kinase MB (CKMB) was significantly elevated immediately postrace for both distances; however, it accounted for less than 5% of the total CK value and in the presence of an elevated total CK and CKMM implied that the elevated CKMB was noncardiac in origin. Troponin-T, however, was significantly elevated immediately postrace for both distances and returned to normal following 48-h recovery indicating myocardial damage. Conclusions: Ironman and half-Ironman competition resulted in reversible abnormalities in resting left ventricular diastolic and systolic function. Results suggest that myocardial damage may be, in part, responsible for cardiac dysfunction, although the mechanisms responsible for this cardiac damage remain to be fully elucidated.